Regional geothermal resource assessment of hot dry rocks in Northern England using 3D geological and thermal models. (November 2022) - Brown, Christopher S.
Highlights: Estimates of the heat in place in the North Pennine and Lake District Batholiths have been made. Probabilistic methods have been used to determine uncertainty when quantifying the geothermal resource. Deterministic methods find the total heat in place to be 2639.9 EJ and the recoverable heat to be 52.8 EJ. Abstract: This study assesses the geothermal potential in Northern England for hot dry rocks, with specific focus to the North Pennine and Lake District Batholiths. The heat in place was estimated using an adapted volume method, which considers a 3D geological and thermal model of the subsurface. Using deterministic methods, the total heat in place was calculated at 2639.9 EJ and the recoverable heat at 52.8 EJ. When considering heat available for electricity generation only, the heat in place was calculated as 1856.1 EJ and recoverable heat as 37.1 EJ. Probabilistic methods were also used to determine uncertainty, but provided similar P50 values to the deterministic average values listed above. The uncertainty range for the total heat in place was determined by the P90-P50-P10 estimates which corresponded to 2572 EJ - 3104 EJ - 3637 EJ. Results from this study offer encouragement that the successful development of hot dry rock prospects can be produced in Northern England where a significant geothermal resource is constrained.